English for Young Learners (EYL) Policy and Practice in ASEAN Countries - Diyanti, B. Yuniar; Madya, Suwarsih (International Journal of Language Education, 2021)
This article compares and discusses the current state of teaching English to young learners (EYL) in ASEAN country members. It pictures the policy and practice of EYL in which English is adopted as either a first, second, or foreign language. The discussion on each country begins with a brief historical and political review that helped shape the countryâ€™s policy on foreign language education. It then moves to the status of English in the polity then to EYL policy and practice of each country and follows next the challenges each country experiences regarding EYL. The final part of the article discusses the implication related to what needs to be done to address these challenges.Â Keywords: EYL policy and practice, English in ASEAN